Outcome prediction for Bonebridge candidates based on audiological indication criteria. Issue 5 (October 2019) - Wimmer, Wilhelm; von Werdt, Moritz; Mantokoudis, Georgios; Anschuetz, Lukas; Kompis, Martin; Caversaccio, Marco
Abstract: Objective: To re-evaluate current indication criteria and to estimate the audiological outcomes of patients with Bonebridge bone conduction implants based on preoperative bone conduction thresholds. Methods: We assessed the outcome of 28 subjects with either conductive or mixed hearing loss (CMHL) or single-sided deafness (SSD) who were undergoing a Bonebridge implantation. We used linear regression to evaluate the influence of preoperative bone conduction thresholds of the better/poorer ear, indication group, and language (German- and French-speaking patients) on aided sound field thresholds. In addition, aided word recognition scores at 65 dB sound pressure level were fit with a logistic model that included preoperative bone conduction thresholds of the better/poorer ear, indication group, and language as effects. Results: We found that both aided sound field thresholds and word recognition were correlated with the preoperative bone conduction thresholds of the better hearing ear. No correlation between audiological outcomes and the preoperative bone conduction thresholds of the poorer ear, language, or indication group was found. Conclusion: Bone conduction thresholds of the better hearing ear should be used to estimate the outcome of patients undergoing Bonebridge implantation. We suggest the indication criteria for Bonebridge candidates considering maximal bone conduction thresholds of the better ear at 38 dB HL to achieve an aided sound field threshold of at least 30 dB hearing level and an aided word recognition score of at least 75% for monosyllabic words.